2018
DOI: 10.1159/000487285
|View full text |Cite
|
Sign up to set email alerts
|

Swiprosin-1 Promotes Mitochondria-Dependent Apoptosis of Glomerular Podocytes via P38 MAPK Pathway in Early-Stage Diabetic Nephropathy

Abstract: Background/Aims: Podocyte injury, especially podocyte apoptosis, plays a major role in early-stage diabetic nephropathy (DN). Swiprosin-1, also known as EF hand domain containing 2 (EFhd2), is a Ca2+-binding protein in different cell types. However, the function of swiprosin-1 in podocytes remains unknown. Methods: The expression and distribution of swiprosin-1 were investigated in the mouse renal glomerulus and conditionally immortalized mouse podocyte cell line MPC-5. The expression of swiprosin-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 59 publications
(70 reference statements)
1
24
0
Order By: Relevance
“…6C–E ). Taken together, our present results correlated to the transcription (mRNA) of Swiprosin-1 gene was upregulated upon treatments, which were previously reported in mast cells, T cells, malignant melanoma cells 1 , macrophage, and glomerular endothelial cells 6 , 9 , 20 . More importantly, we notified that all CNS-1, -2 and -3 upregulate the transactivation of −141 bp proximal promoter region of Swiprosin-1 compared with the -141/Sw-1 alone (without conjugated with CNS) even in the absence of above treatments, and CNS-3 was most predominant among them (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…6C–E ). Taken together, our present results correlated to the transcription (mRNA) of Swiprosin-1 gene was upregulated upon treatments, which were previously reported in mast cells, T cells, malignant melanoma cells 1 , macrophage, and glomerular endothelial cells 6 , 9 , 20 . More importantly, we notified that all CNS-1, -2 and -3 upregulate the transactivation of −141 bp proximal promoter region of Swiprosin-1 compared with the -141/Sw-1 alone (without conjugated with CNS) even in the absence of above treatments, and CNS-3 was most predominant among them (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…This result was correlated with that the Swiprosin-1gene expression was not upregulated in mouse B cells upon anti-IgM F(ab)2/IL-4, LPS or anti-CD40/IL-4 12 . However, our previous studies and others reported that endogenous Swiprosin-1gene expression was specifically upregulated in human mast and T cells up on PMA or A23187 or PMA/A23187 stimulation and also in malignant melanoma cells upon EGFR stimulation 2 , 6 , 7 , 9 , 11 . Swiprosin-1 gene expression was very broad and also its expression level was tissue or cell type specific of various organisms 1 , 9 , 19 , 20 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The kidney is composed of tubules, renal vesicles, and glomeruli. Studies have reported that kidney injury is mainly caused by glomerular or tubular apoptosis [ 53 , 54 ]. However, whether DEX alleviates apoptosis induced by acute stress in tubular cells or glomerular cells is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the GO enrichment analysis results, the potential targets of shenzhuo formula acting on DN were mainly associated with various biological processes, such as lipopolysaccharide-mediated signaling pathway, inflammatory response, positive regulation of cyclase activity, protein kinase B signaling, positive regulation of MAP kinase activity, response to estradiol, which have a strongly direct correlation with the pathogenesis of DN [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 95%